Cargo Services Equipment Utilization And Operational Efficiency In Improving Port Concession Revenue - Simanjuntak, Rita; Jinca, Muhammad Yamin; Olfebri, Olfebri; Sonny, Imam (Dinasti International Journal of Education Management and Social Science, 2026)
Ports play a vital role in supporting global logistics and trade activities, where operational efficiency becomes a key determinant of port competitiveness and financial performance. This study aims to examine the influence of cargo services and equipment and facility utilization on operational performance and port concession revenue. The research employs a mixed-method approach with an explanatory sequential design. Quantitative analysis was conducted using secondary operational data based on the Operational Service Performance Standards at Tanjung Priok Port and processed using SPSS and EViews through classical assumption tests, path analysis, and hypothesis testing. The qualitative stage involved structured in-depth interviews with regulators, port operators, and service users to explore the roles of regulations, policies, and digital technologies such as the Internet of Things (IoT). The results indicate that equipment and facility utilization significantly improves operational performance and port revenue, while cargo services positively influence revenue but may reduce operational efficiency when operational coordination is inadequate. Operational performance also plays a significant mediating role. Overall, improving operational efficiency, infrastructure utilization, and digital integration is essential to enhance port concession revenue.